Fractographic analysis of broken ceramic dental restorations - Quinn, George D.; Hoffman, Kathleen; Scherrer, S.; Lohbauer, Ulrich; Amberger, G.; Karl, Matthias; Kelly, J. R. (Ceramic Transactions, 2012)
Three in vivo fractured multiunit all-ceramic restorations were analyzed as part of an ongoing project to characterize fracture mechanisms in dental restorations. The overall breakage patterns were evaluated and stereoptical and scanning electron microscopy used to find the origins of fracture. The causes of fracture in the alumina and zirconia restorations were different in each case.
CRIS-Team Scopus Importer:2023-01-23